Crystal structures and intense luminescence of tris(3-(2′-pyridyl)-pyrazolyl)borate Tb3+ and Eu3+ complexes with carboxylate co-ligands. Issue 11 (31st January 2017) - Mikhalyova, Elena A.; Yakovenko, Anastasiya V.; Zeller, Matthias; Gavrilenko, Konstantin S.; Kiskin, Mikhail A.; Smola, Sergey S.; Dotsenko, Vladimir P.; Eremenko, Igor L.; Addison, Anthony W.; Pavlishchuk, Vitaly V.
Abstract : The carboxylate coligands affect the bright luminescence of a series of Eu 3+ and Tb 3+ complexes. Abstract : A series of brightly luminescent new mononuclear Tp Py Ln(An)2 (H2 O) (where An − = carboxylate anion, Ln = Eu or Tb and Tp Py− = tris(3-(2′-pyridyl)pyrazolyl)borate) and dinuclear (Tp Py Ln)2 pma(MeOH)2 (Ln = Eu, Tb, pma 4− = tetraanion of pyromellitic acid) complexes were prepared and characterized by X-ray crystallography. Within each series the compounds possess similar molecular structures, which differ only by the nature of the carboxylate anions. The quantum efficiencies for metal-centered emission of the complexes were up to 29(3)% for Eu 3+ and 53(5)% for the Tb 3+ compounds and significantly depend on the electronic structure of the additional ligand ( i.e. the carboxylate). The aliphatic carboxylate compounds' luminescence quantum yields were all similar, but different from those for the aromatic ones. The complexes with trifluoroacetate and pentafluorobenzoate unexpectedly displayed lower quantum efficiencies compared to those with the corresponding non-fluorinated analogues. Energy transfer from Tb 3+ to Eu 3+ occurs in a mixture of (Tp Py Eu)(pma)(TbTp Py )(MeOH)2, (Tp Py Eu)2 (pma)(MeOH)2 and (Tp Py Tb)2 (pma)(MeOH)2 but is not very efficient. The Tb 3+ -compounds displayed green electroluminescence, and both the Eu 3+ and Tb 3+ complexes exhibited bright metal-centered red (Eu 3+ ) or green (Tb 3+ ) triboluminescence.